The Determinants of Tourism Demand in Turkey - Abedtalas, Musallam (Journal of Economics and Behavioral Studies, 2015)
Using data of the inbound tourist arrivals to Turkey from France, Germany, UK, US, and Netherlands over the period 1986-2012, we applied autoregressive distributed lag (ARDL) approach to test for cointegration, and we estimated long run model and error correction model for tourism demand. The results referred that the most significant factor determines inbound tourist flows are the real per capita income and real effective exchange. We found weak effects for price and financial crisis, but the political events played a strong role differed from country to other. The added value of this article is the estimation of international tourism demand in Turkey using new approach and the newest data for Turkey